2013
DOI: 10.1590/s0034-71672013000400017
|View full text |Cite
|
Sign up to set email alerts
|

Acidentes e violências na infância e adolescência: fatores de risco e de proteção

Abstract: RESUMOApontada pelas estatísticas como a terceira causa de mortalidade em nosso país, as causas externas (acidentes e violências) ocasionam um grande impacto com repercussão econômica, social e emocional. Conhecer os fatores relacionados a este evento torna-se essencial, pois possibilita identifi car e quebrar a teia que determina a morbimortalidade por causas externas. O estudo busca analisar as publicações existentes sobre os fatores associados aos acidentes e violências, a fi m de proporcionar subsídios teó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
20

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 55 publications
(66 reference statements)
0
9
0
20
Order By: Relevance
“…1,5,7,10 One study undertaken in Ontario, Canada, with children aged from 6 to 11 years old, observed that the boys are significantly more involved in risky activities than are girls, 12 as the boys present more impulsive behaviors, allied with the cultural fact that the parents and guardians restrict the boys' behavior less in comparison with the girls, who are supervised more, in spite of the boys' activities and games being judged as of greater risk for accidents. [12][13] The greater incidence of accidents resulting from inanimate mechanical forces among children aged from one to four years old is corroborated by other cases. 7,[14][15][16] Children in this age range begin to interact with the domestic environment, place objects in their mouths and in other orifices, present curious behavior and, due to their neuropsychomotor development, cannot yet foresee situations of risk and protect themselves in the event of danger.…”
Section: Discussionmentioning
confidence: 77%
“…1,5,7,10 One study undertaken in Ontario, Canada, with children aged from 6 to 11 years old, observed that the boys are significantly more involved in risky activities than are girls, 12 as the boys present more impulsive behaviors, allied with the cultural fact that the parents and guardians restrict the boys' behavior less in comparison with the girls, who are supervised more, in spite of the boys' activities and games being judged as of greater risk for accidents. [12][13] The greater incidence of accidents resulting from inanimate mechanical forces among children aged from one to four years old is corroborated by other cases. 7,[14][15][16] Children in this age range begin to interact with the domestic environment, place objects in their mouths and in other orifices, present curious behavior and, due to their neuropsychomotor development, cannot yet foresee situations of risk and protect themselves in the event of danger.…”
Section: Discussionmentioning
confidence: 77%
“…6,11,12 As diferenças comportamentais de cada sexo e fatores culturais que determinam mais liberdade aos meninos e, em contrapartida, mais vigilância às meninas poderiam justificar esses achados. 8 A maior prevalência das mortes por causas externas na raça/ cor não branca também foi observada em outros estudos. Esse aspecto precisa, entretanto, de mais aprofundamento, já que diferenças de níveis socioeconômicos, entre as raças, no Brasil são desfavoráveis para a raça/cor não branca.…”
Section: Discussionunclassified
“…7 As características desses óbitos podem variar conforme a idade da vítima, sexo, cor ou raça e outros fatores. 8 Há previsão de que o número de mortes por causas externas em crianças irá crescer dramaticamente em decorrência de mudanças no ambiente e no aumento da exposição ao risco, especialmente em países em desenvolvimento. 3 Considerando a magnitude das causas externas no cenário da morbimortalidade infantil e que a maioria dos óbitos poderia ser evitada com a adoção de medidas preventivas, realizou-se o presente estudo com o objetivo de identificar perfis de mortalidade por causas externas em crianças de um a nove anos residentes em Minas Gerais.…”
Section: Introductionunclassified
“…Um menino adolescente tem duas vezes mais chances de sofrer um acidente do que uma menina com a mesma idade (BEM et al, 2008). A maior predisposição do sexo masculino aos acidentes e violências também é reportada em outros estudos (GASPAR et al, 2012;MARTINS, 2013).…”
Section: Discussionunclassified